Evaluation of Adjunctive Low Level Laser Therapy in Postoperative Management of Pain, Swelling, Trismus Following Surgical Removal of Impacted Mandibular Third Molars: Life Sciences-Health - R, Sailesh Kumar; P, Manodh (International Journal of Life Science and Pharma Research, 2022)
Our aim is to evaluate the effectiveness of Low Level Laser Therapy (LLLT) in the control of postoperative pain, swelling, and trismus associated with the surgical removal of impacted mandibular third molars. This study was carried out as a single centre, prospective study with a sample size of 30 patients to evaluate the effectiveness of LLLT following surgical removal of impacted third molars. Patients were randomly divided into two groups of 15 each. Group 1(Study /LLLT group) consisted of patients undergoing LLLT and with the use of postoperative analgesics and antibiotics. Group 2 (Control) included patients who were administered postoperative analgesics and antibiotics without the concurrent use of LLLT. The predictor variable was the LLLT application following mandibular third molar impaction surgery. The outcome variables namely pain, swelling, and trismus were evaluated on the day of surgery and 1st, 3rd, and 7th postoperative days (POD).Results:The pain was highest on POD 1 and gradually reduced by POD 7 in the study group when compared to the control group. Swelling showed a steep increase on POD 1 and thereafter a gradual reduction was observed on POD 7, when compared to the control group, the study group showed a significant decrease in swelling. Mouth opening was the lowest on POD1 and gradually increased by POD 7 in the study group than in the control group. Conclusion: The results of the study suggest that the application of LLLT to impacted mandibular third molar sockets helps eliminate/or reduce postoperative pain, swelling, and trismus.